Elucidating the genetic relationship between ulcerative colitis and diabetic kidney disease: a bidirectional Mendelian randomization study - Guo, Yaping; Yu, Hangxing; Li, Ying; Zhang, Taijun; Xiong, Weijian; Wu, Xili (Frontiers in Endocrinology, 2024)
Ulcerative colitis (UC) and diabetic kidney disease (DKD) are chronic disorders characterized by complex pathogenesis, presenting substantial challenges in clinical management. Despite extensive investigations into their respective causes, the interplay between UC and DKD remains poorly elucidated. This study seeks to clarify the genetic association between UC and DKD using Mendelian randomization (MR) analysis, providing new insights into common pathways and potential clinical implications. A bidirectional two-sample MR study was conducted using data from large-scale genome-wide association studies (GWAS) for UC and DKD. Instrumental variables (IVs) were rigorously selected based on genome-wide significance and stringent criteria to ensure robust causal inference. Various MR methods, including inverse variance weighting (IVW), were applied to evaluate causal relationships between UC and DKD. Sensitivity analyses were performed to validate the results. Our findings demonstrate a significant causal link between genetic predisposition to UC and increased susceptibility to DKD. Specifically, individuals with genetic susceptibility to UC exhibited a 17.3% higher risk of developing DKD. Conversely, no causal relationship was observed between DKD and the risk of UC. Moreover, shared genetic risk factors and molecular pathways between UC and DKD were identified, highlighting potential targets for therapeutic intervention. This study underscores the intricate genetic interplay between UC and DKD, suggesting that UC may predispose individuals to the development of DKD. Understanding these shared pathways could guide early detection strategies and targeted interventions for individuals at risk of DKD, thereby improving outcomes for both conditions.